Implications of the uruguay round agreement for South Asia the case of agriculture - Blarel, Benoit (Ed.); World Bank (Washington); Pursell, Garry (Ed.); Valdes, Alberto (Ed.) (Washington World Bank, 1999)
This volume brings together the main papers presented at workshop, which covered South Asia and was held in Kathmandu Nepal, during 22-24 April, 1996. It has four main sections: The First comprises overview papers prepared by International Economics Divis
World Bank/FAO workshop held in Kathmandu, May, 1996
Keywords: Agriculture; Agriculture and state-South Asia; Uruguay round (1987-1994); Agricultural development projects; Agricultural development projects-India